Comparison of diabetes‐associated secondary healthcare utilization between alternative oral antihyperglycaemic dual therapy combinations with metformin in patients with type 2 diabetes: an observational cohort study. Issue 6 (6th April 2015) - Strongman, H.; D'Oca, K.; Langerman, H.; Das, R.
<x xml:space="preserve">Abstract</x> Aims To compare diabetes‐associated secondary healthcare utilization in patients with type 2 diabetes (T2DM) prescribed sulphonylureas (SUs) versus other oral antihyperglycaemic agents (OHAs) as an add‐on to metformin monotherapy (metformin + SU vs metformin + OHA). Methods This retrospective cohort study used data from the Clinical Practice Research Datalink linked to Hospital Episode Statistics. Adults with T2DM initiated on metformin + SU or metformin + OHA from April 2003 to March 2012 were identified. Patients were matched using propensity scores. Diabetes‐associated secondary healthcare visits were counted from >6 months post‐initiation of dual therapy until treatment change or end of follow‐up. Outcomes were calculated as rate ratios, adjusted for over‐dispersion using negative binomial regression and propensity score for covariates. Results After propensity score matching, 1704 patients were included in each cohort. For the primary objective (diabetes‐associated inpatient and outpatient visits combined), the metformin + SU cohort had a directionally higher rate of diabetes‐associated secondary healthcare utilization than the metformin + OHA cohort [adjusted rate ratio 1.12, 95% confidence interval (CI) 0.97–1.29]. For the secondary outcomes, the adjusted rate ratio was 1.38 (95% CI 0.95–2.00) for inpatient admissions and 1.10 (95% CI 0.95–1.28) for outpatient visits. Macrovascular complications, accounting for 77.2% of inpatient admissions, occurred at a statistically significantly higher rate in the metformin + SU cohort than in the metformin + OHA cohort (adjusted rate ratio 1.77, 95% CI 1.15–2.71). Conclusions This study found a statistically significant higher rate of inpatient admissions for macrovascular complications and cardiology outpatient visits and, overall, a directionally higher rate of secondary healthcare utilization for patients prescribed metformin + SU than for those prescribed metformin + OHA. This adds to the evidence that long‐term and health economic outcomes should be considered in treatment decisions for patients with type 2 diabetes.